KONSTELASI NARASI TENTANG KETAHANAN PANGAN DALAMPROGRAM FOOD ESTATE DI EKS PLG KALIMANTAN TENGAH:DIMANAKAH NARASI PELADANG PEREMPUAN? - Evi Nurleni (Prodi Sosiologi FISIP UPR, 2021)
The media plays a role in opinion, perceiving and orienting an issue to the majority or audience. Meanwhile, the forms of opinion, perception and orientation from the media become narratives that are formed in a constellation that “fights” each other. Narrative battles are formed as an effort to seize public space that can influence perceptions and interests, even policies at the state level. In this case, the food estate narrative in Central Kalimantan is understood as a constellation or narrative battle to seize the space of “power” and interest. The food estate program is in a battle of dictions between the interests of the government which is oriented towards modernization, development and progress, against the interests of civil society which is oriented towards the environment, local interests and indigenous peoples. The battle of these dictions is a battle of grand-narratives that forgets small and local narratives, namely female cultivators. Dayak cultivators themselves have long been narrated as a group that destroys forests, primitive communities and the unmodern people, so they are not at the forefront of discussing development issues. Meanwhile, the suffering of Dayak cultivators woman disappears in the grand narrative or becomes a silent group or subaltern.